The Influence Of Social Influence And Product Variations On Purchasing Decisions Ideania Flowery In Ponorogo With Purchase Intention As An Intervening Variable - Rita Tsaniatul Munawwaroh; Siti Chamidah; Wijianto Wijianto (Jurnal Manajerial, 2025)
Background - The development of the creative economy in Indonesia has shown a significant increase. One sector that is experiencing rapid growth is the florist industry. In an increasingly competitive florist industry, businesses such as Ideania Flowery face challenges to stay ahead in a growing market. Factors such as social influence and product variety are important elements in influencing consumer purchasing decisions. Aim - The purpose of this study is to prove the relationship between social influence variables and product variations on purchasing decisions and how the role of purchase intention as a mediating variable on the influence of social influence and product variations on purchasing decisions, and how the role of purchase intention as a mediating variable on the influence of social influence and product variations on Ideania Flowery consumer purchasing decisions. Design/ Methodology/ Approach - This research is a quantitative research with data collection method using questionnaires distributed through google form to 84 respondents from Ideania Flowery consumers with purposive sampling technique. Data measurement uses a Likert scale of one to five. The data analysis used in this research is SEM (Structural Equation Modelling) through the SMART PLS 4.0 application with a mediation analysis model. Findings - The results showed that social influence has a significant effect on buying interest of Ideania Flowery consumers, product variations have a significant effect on buying interest of Ideania Flowery consumers, social influence has a significant effect on purchasing decisions of Ideania Flowery consumers, product variations have an insignificant effect on purchasing decisions of Ideania Flowery consumers, purchase interest has a significant effect on purchasing decisions of Ideania Flowery consumers and purchase interest acts as a mediator on the effect of social influence on purchasing decisions, and purchase interest acts as a mediator on the effect of product variations on purchasing decisions of Ideania Flowery consumers. Research Implications - This research has a significant impact on consumers and the company Ideania Flowery, and can provide benefits for consumers in providing education to be wiser in making purchasing decisions, by paying attention to needs and not just social influence or the attractiveness of diverse products. Then it will be useful for the company Ideania Flowery, more complete knowledge about the influence of social influence and product variety in influencing purchasing decisions, so that it can help companies to develop more effective marketing strategies. Not only that, the company can also provide added value through products and can strengthen consumer attractiveness and encourage sales. Research Limitations - This study only involved 84 respondents who are consumers of Ideania Flowery in Ponorogo, so the results may not apply to consumers in other areas.